PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA PADA BUMDESA DI KABUPATEN BOJONEGORO - Arief Budi Wardana (Jurnal Abdi Mandala, 2023)
One of the problems faced by BUMDes is the inadequate condition of human resources, especially for presenting financial reports. PKN STAN together with DPMD Provinsi Jawa Timur and DPMD Kabupaten Bojonegoro held Community Service activities to increase the capacity of Human Resources in the accounting field at BUMDes in Bojonegoro. The series of activities involving 17 BUMDes started with offline training and visitations, followed by online mentoring for a period of 2 months. The training activities have succeeded in increasing the participants' abilities by increasing the post-test scores compared to the pre-test. In addition, the BUMDes that were visited received several suggestions for improvement and continued with discussions to answer the problems encountered when using the BUMDes Accounting Application.